Peran Pertanian dalam Pengembangan Ekonomi: Penilaian Transformasi Struktural dan Dinamika Pertumbuhan Ekonomi - Syahputri, Dian Afriyanti (Nomico, 2024)
By understanding the role of agriculture in economic development holistically, this research aims to provide policy makers, practitioners, and academics with deeper insights on how to enhance the role and contribution of the agricultural sector in achieving inclusive and sustainable economic growth. Through a careful evaluation of the structural transformation and dynamics of economic growth in the agricultural sector, this research is expected to provide valuable guidance in formulating more effective and future-oriented policies. In this study, the use of qualitative methods involved a variety of techniques and approaches. By using these qualitative methods, the research was able to explore various complex aspects of how agriculture plays a role in economic development, including the challenges, opportunities, social dynamics, and policies that affect it. Research results The agricultural sector is an important part of a country's economic structure, involving a wide range of activities from production to distribution of agricultural products. While agriculture is often the dominant sector in the early stages of economic development, its role continues to change as the economy develops. The role of the agricultural sector is crucial in feeding the population, creating jobs, and contributing to economic growth, especially in developing countries. However, agricultural activities can also have significant impacts on the environment, such as land degradation and ecosystem damage.